2011
DOI: 10.4194/trjfas.2011.0115
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Studies were conducted on the growth and mortality parameters, recruitment pattern, probability of capture, yield-per recruit, and present rate of exploitation of the African river prawn, Macrobrachium vollenhovenii from Dawhenya impoundment, Ghana. Estimation of the von Bertalanffy growth parameters gave; L ∞ = 14.2 cm, K = 1.0 yr-1 , and t o =-0.195 yr-1 with the growth performance index, Ф' of 2.303. From the linearised length-converted catch curve, total mortality, Z was 5.36 yr-1. Natural mortality, M cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
4
2
Order By: Relevance
“…This variation in growth performance in the two populations of M. macrobrachion could be justified by the differential growth in size within individuals of the same age as well as by the modifications of the physical and chemical parameters of the water of each site (Zinsou et al, 2016), which can influence the growth of individuals (Gabche & Hockey, 1995). The values of Ф′ obtained in the present study are lower than the values estimated for other stocks of palaemonid prawn species, in particular, species of the genus Macrobrachium such as M. vollenhoveni (Ф′ = 2.303) (Alhassan & Armah, 2011). The estimated Ф′ values in this study indicate that M. macrobrachion from the two study environments could be classified in the group of species with low growth.…”
Section: Demographic Parameters Of Growthcontrasting
confidence: 90%
See 3 more Smart Citations
“…This variation in growth performance in the two populations of M. macrobrachion could be justified by the differential growth in size within individuals of the same age as well as by the modifications of the physical and chemical parameters of the water of each site (Zinsou et al, 2016), which can influence the growth of individuals (Gabche & Hockey, 1995). The values of Ф′ obtained in the present study are lower than the values estimated for other stocks of palaemonid prawn species, in particular, species of the genus Macrobrachium such as M. vollenhoveni (Ф′ = 2.303) (Alhassan & Armah, 2011). The estimated Ф′ values in this study indicate that M. macrobrachion from the two study environments could be classified in the group of species with low growth.…”
Section: Demographic Parameters Of Growthcontrasting
confidence: 90%
“…The different values of the mortality parameters estimated in the present study are much lower than those reported by Enin (1995) in the same species in Nigeria and by Alhassan and Armah (2011) for M. vollenhoveni in Ghana. This difference in mortality could be linked to the phenomenon of emigration because this phenomenon sometimes appears as apparent mortality, although it can be compensated by the phenomenon of immigration (Laevastu & Favourite, 1988).…”
Section: Mortalitiescontrasting
confidence: 86%
See 2 more Smart Citations
“…Also, males attain a smaller body size than females: 12 and 32 mm CL, two and 12 months after larval settlement, respectively. Previous studies have reported rapid growth rates in other species of Macrobrachium (Kanaujia et al 1997;Romero and Silva 2008;Alhassan and Armah 2011) (see review in Table 4 (1970) who reported an initial body size of 6.5 mm total body length (TL) and 27 mm TL for juveniles 40 days and two months after metamorphosis, respectively (data obtained from laboratoryreared specimens after larval development). Using previously published equations that relate CL to TL (CL ¼ 0.533 Â TL and CL ¼ 0.5043 Â TL in males and females, respectively: Albertoni et al 2002), our results fit well with those previously reported by Choudhury (1970) for males but not for females.…”
Section: Discussionmentioning
confidence: 99%